Land Planning and Site Plane Creation, Faculty of Engineering, University of Muhammadiyah Buton - Sayfullah. S, Muh.; Efendi, Ahmad; Agusman (Room of Civil Society Development, 2023)
Measurement of land development at the Faculty of Engineering, University of Muhammadiyah Buton is carried out to determine the condition of the land that will be used as a reference for developing, structuring land and planning from the University. Measurement method using the Theodolite tool.  With the division of  benchmark  points (BM) in accordance with the conditions in the development land of the Faculty of Engineering. The measurement results can be used as a reference to carry out development planning appropriately. Processing is carried out in several stages, starting from literature studies, field surveys, data collection, measurement, data processing, to results and conclusions. The measurement process is carried out in several stages ranging from the manufacture and installation of benchmark  (BM) benchmarks, BM point determination, site up Theodolite tools and detailed measurements. The results of this service activity are in the form of a development site plane plan image, elevation plan, and  3D view image. The measurement images can be used as a reference in carrying out future development of the land development of the Faculty of Engineering, University of Muhammadiyah Buton.